Thursday, March 19, 2009

Sum of Geometric Series


In our proof that repeating numbers are rational, we used the following relationship:

S = Sum of the geometric series arn-1
= a + ar1 + ar2 + ar3 + ar4......
= a/(1-r)

Where does this rather elegant and surprising relationship come from ? Certainly, this simple realtionship is rather unexpected .... why would an infinite series converge on this simple ratio ?

Like many relationships in mathematics, the proof is beautifully simple. Firstly, form the equation S - Sr = a + ar1 + ar2 + ar3 ..... - ar1 + ar2 + ar3 .... = a

Therefore, rearranging we arrive at S = a/(1-r).


QED

1 comment: